Strategic thinking by non-government organisations for sustainability : a review of the logical framework approach - Muspratt-Williams, Angela (Stellenbosch : University of Stellenbosch, 2009)
Thesis (MPhil (Sustainable Development Planning and Management))--University of Stellenbosch, 2009.